2021
DOI: 10.2166/wst.2021.371
|View full text |Cite
|
Sign up to set email alerts
|

Study on pollution characteristics of urban pavement runoff

Abstract: Urban pavement runoff has become an important pollution source to endanger the quality of urban water. This paper analyzed the characteristics of particle size distribution of road-deposited sediment (RDS). The variation of pollutants contented with RDS was presented. Based on continuous sampling of runoff, the variation between pollutant concentration and rainfall characteristics was revealed. The results show that each particle group shares similar content except for the group smaller than 0.075 mm. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In order to obtain the artificial pavement runoff pollutant required for the indoor scaled down model, sediment was collected from the curbstone of the entrance to Wanjiali South Road, Changsha Bypass Expressway, China, at a range of 0-50 cm. This is because most of the road sediment is deposited at both sides of the road within 50 cm of the curbstone [31]. The collected area was 5 m 2 .…”
Section: Preparation Of Artificial Pavement Runoff Pollutantmentioning
confidence: 99%
“…In order to obtain the artificial pavement runoff pollutant required for the indoor scaled down model, sediment was collected from the curbstone of the entrance to Wanjiali South Road, Changsha Bypass Expressway, China, at a range of 0-50 cm. This is because most of the road sediment is deposited at both sides of the road within 50 cm of the curbstone [31]. The collected area was 5 m 2 .…”
Section: Preparation Of Artificial Pavement Runoff Pollutantmentioning
confidence: 99%
“…In his research, Mamoon also evaluated the formation of the first effluent in an urbanized area, finding that the largest mass of pollutants was the 1252 (2022) 012075 IOP Publishing doi:10.1088/1757-899X/1252/1/012075 4 first 40 % runoff [3]. Qian et al (2021), in their research, they assessed the mass of pollutants trapped in the first 30 % runoff. They have found that in the first 30 % of runoff, is occurring 36 % to 90 % of pollutants (depending on the characteristics of pollutants, rain, and land use) [18].…”
Section: Evaluation Of the First Flushmentioning
confidence: 99%
“…Qian et al (2021), in their research, they assessed the mass of pollutants trapped in the first 30 % runoff. They have found that in the first 30 % of runoff, is occurring 36 % to 90 % of pollutants (depending on the characteristics of pollutants, rain, and land use) [18]. In their study, Huang et al (2012) verified that the first 30 runoff volumes carried the largest mass of pollution.…”
Section: Evaluation Of the First Flushmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the TOC value is highly variable [40]. The positive correlation between the concentration of a few organic pollutants and non-organic with TOC% has been announced by numerous researchers in their surveys [41][42][43][44][45].The combination and heavy metal distribution is affected by the particle size distribution of sediments in runoff [46][47][48][49].Generally, less particles have a further speci c surface area to deposit heavy metals and to adsorb higher heavy metal concentrations in comparison with larger particles [50][51][52][53]. The particle sediments with a size less than 63 micrometers(63µm>) can attach to human skin, which is a problem for human health [46,47].…”
Section: Introductionmentioning
confidence: 99%